Dimensi-Dimensi Sosiologis Migrasi Buruh Migran Perempuan Indonesia - Ayu Kusumastuti; Lynn Thiesmeyer (Sociology Department, Brawijaya University, 2020)
AbstrakArtikel ini berusaha untuk menjelaskan dimensi-dimensi sosiologis buruh migran perempuan yang bekeja di sektor Domestik di Indonesia. Indonesia adalah negera terbesar pengirim buruh migran perempuan domestik di Dunia. Banyaknya tenaga kerja yang dikirim ini, terkait dengan kondisi di perdesaan yang dianggap kurang bisa memenuhi kebutuhan hidup. Dengan analisa sosiologis, artikel ini berusaha menjelaskan dengan kerangka mikro melaui analisa deprivasi relatif individu, dalam kerangka meso melalui penjelasan tentang perubahan interaksional dalam keluraga buruh migran perempuan dan terakhir dengan penjelasan makro yaitu pada bekerjanya sistem nilai, norma, kepercayaan dan jaringan dalam sistem migrasi.Kata kunci: buruh migran perempuan, deprivasi, perubahan sosial, sistem sosialAbstractThis article attempt to describe sociological dimensions of Indonesia female migrant workers working in the domestic sector. Indonesia is the largest sending country of female migrant worker in the world. The large ammount of female workers sent to overseas has related with the condidtion in the rural area considered less able to fulfill the people needs. With the sociological analysis, this article tries to explain with the micro framework through individual relative deprivation analysis. In the messo framework, it will be explained by interactional social change in the female migrant workers family. In the end, this article also completes the analysis with macro analysis that emphasizes on the work of social value, social norm, trust and network in migration system.Â Keywords: female migrant worker, deprivation, social change, social system